G.E. Moore’s Principia Ethica and the complex of architecture - Tim Gough (Footprint)
G.E. Moore’s Principia Ethica of 1903 is generally regarded as a starting point of analytical philosophy.  It’s concern with analytical propositions, the pushing of analysis to an end point, its rigorous style, the clarity of its arguments and the precise demolition of the less-than-rigorous work of preceding philosophers provided a template for how twentieth century Anglo-Saxon thought might forge its own path.